Science-policy-practice interaction - Päivinen, Risto (Natural Resources Institute Finland, Luke, 2016)
In national and international forest-related policy processes, it has been widely recognized that decisions must be based on the best available scientific knowledge. In order to generate added value for people and society, science must be utilized in the design and implementation of decisions by policy-makers and forest practitioners at all levels. The manner in which research results have been used to support the selection of policy targets for bioeconomy and ecosystem services varies from country to country. The international and national mechanisms established to this point in time have increased dialogue between researchers, policy-makers and practitioners. They aim at boosting the effectiveness of research investments by accelerating the process between research and implementation of the results. The levers include analyzing the often scattered research results and synthesizing them with a set of policy options and recommendations. Further, the analysis of available information also reveals the need for further research. The communication tools include brief documents with clear recommendations, panels, including fora, and conferences of various types and sizes. Some examples on that how the new knowledge provided by research can be used by European policy-makers and practitioners are described and discussed.
Keywords: science-poilicy-practice interaction; impact of research; scientific communication